Improving lecturers' competence in writing nationally accredited scientific papers - Muhamad Uyun (Universitas Muhammadiyah Magelang, 2023)
Lecturers are required to produce scientific papers for improving their careers. However, there are many lecturers who do not understand how to write scientific papers and to publish it. This community service aims to improve the competence of lecturers in writing scientific papers so that they can make good scientific papers and can publish it. The program is carried out in two stages: 1) preparation stage, and 2) implementation through training on writing scientific paper. The results showed that the participants were able to understand 1) the basics of scientific writing, 2) the parts of scientific articles, 3) the scientific publication policies, 4) the criteria and requirements for publishing scientific papers in accredited journals, 5) the paraphrase techniques, 6) the citation using Mendeley, and 7) the technique of compiling according to the standard template of accredited journals.